Game theory based forwarding control method for social network - Fangfang SHAN; Hui LI; Hui ZHU (Tongxin xuebao)
With the rapid development of mobile communication and internet technology,the social network has become one of the mainstream social means used in people’s daily social life.To maintain and strengthen relationships with friends,users may share personal behavior and feelings through social networks.Forwarding these contents may result in privacy leakage.To help publishers make proper data forwarding decision,the benefits of both sides of the forwarding operation were analyzed,and a game theory based forwarding control method for social network was proposed which could effectively prevent dishonest data forwarding operation.By analyzing the benefits of both sides of forwarding operation and considering historical information,the probability of dishonest data forwarding operation was calculated and it was compared with the threshold set by publisher to make the forwarding decision.The procedure and framework of the game theory based forwarding control method was introduced.The benefits of both sides were defined and analyzed.The game play scenario was presented.Some results of experiments are shown to support that the method is effective and it can protect the security of content in social network.